If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(6y+4)-(-5y-6)=-2
We simplify the equation to the form, which is simple to understand
-(6y+4)-(-5y-6)=-2
Remove unnecessary parentheses
-6y-4-(-5y-6)=-2
Remove unnecessary parentheses
-6y-4+5y+6=-2
We move all terms containing y to the left and all other terms to the right.
-6y+5y=-2+4-6
We simplify left and right side of the equation.
-1y=-4
We divide both sides of the equation by -1 to get y.
y=4
| 8(5+4)= | | -3x+21=3x-21 | | x^4-10x^2-96=0 | | -50z-0.2=-60z+1.4 | | 8n-(3n+8)=32 | | -6y-1=5y-2 | | -[8x-(2x+7)]=1-(9x+3) | | 12+33=-5(2x-9) | | 3(7-x)-33=21x-4(3+6x) | | -8-(-n)=1 | | 8+24=-4(6x-8) | | -175=-29x-30 | | 2x^3-2x+9x^2-24x=0 | | 12x-3=24+5 | | 5x(4x+45)=360 | | -175=-29-30 | | 8n-(6n+7)=1 | | 2x^3-2x+9x^2-24=0 | | (t-1)(t+2)=0 | | 4(3x+9)=-31+7 | | 2/3-6h=13/6 | | -6x^2+15x=0 | | 10z-z=-3+2z-2-2 | | 33-12x=4x-97 | | 4.4x+55.9=16.3-8.8x | | 6x+5+8x-1=11y+13 | | 15x^3-25x^2-10x=0 | | 10z-z=-3+2z-2-9 | | 2(x+5)=6(2x+5) | | 10=-15+x | | 2x+17=9x+45 | | 7(a-8)=7a-56 |